Is PPAR𝛾 a Prospective Player in HIV-1-Associated Bone Disease? - Eoin J. Cotter; Patrick W. Mallon; Peter P. Doran (PPAR Research)
Currently infection with the human immunodeficiency virus-1 (HIV-1) is in most instances a chronic disease that can be controlled by effective antiretroviral therapy (ART). However, chronic use of ART has been associated with a number of toxicities; including significant reductions in bone mineral density (BMD) and disorders of the fat metabolism. The peroxisome proliferator-activated receptor gamma (PPAR𝛾) transcription factor is vital for the development and maintenance of mature and developing adipocytes. Alterations in PPAR𝛾 expression have been implicated as a factor in the mechanism of HIV-1-associated lipodystrophy. Both reduced BMD and lipodystrophy have been well described as complications of HIV-1 infection and treatment, and a question remains as to their interdependence. Interestingly, both adipocytes and osteoblasts are derived from a common precursor cell type; the mesenchymal stem cell. The possibility that dysregulation of PPAR𝛾 (and the subsequent effect on both osteoblastogenesis and adipogenesis) is a contributory factor in the lipid- and bone-abnormalities observed in HIV-1 infection and treatment has also been investigated. This review deals with the hypothesis that dysregulation of PPAR𝛾 may underpin the bone abnormalities associated with HIV-1 infection, and treats the current knowledge and prospective developments, in our understanding of PPAR𝛾 involvement in HIV-1-associated bone disease.